Global Financial crisis and its impact on the performance of the Emerging Stock Exchange: الاردن نموذجا (Journal of Accounting and Financial Studies ( JAFS ), 2010)
The research aims to explain the reality and the roots of the problem financial crisis and its impact on the performance of the Amman Stock Exchange, by testing three hypotheses, the first and the second relates to the performance of the Amman Stock Exchange and its sectors before and after the financial crisis. And the third examined the relationship between indirect foreign investment and the performance of Amman Stock Exchange.      Hypothesis testing results of the first and second pointed to the existence of statistically significant differences for the performance of the stock market in general and in particular their performance for the period before and after the financial crisis. The third hypothesis results revealed that the indirect foreign investment played a role in the performance of the Amman Stock Exchange was positive for the period before the crisis and negative after a crisis.Keyword: Sub prime Mortgage, Sub prime Crisis, Securitization, Mortgage – Backed Securities (MBS), Collateralized Debt Obligation (CDOS), Event study